PENGARUH MOTIVASI KERJA, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KECAMATAN KALIWUNGU SELATAN - Dyah Supriyati, 12.05.51.0102 (Students' Journal of Economic and Management, 2017)
The purpose of this study was to determine the effect of work motivation, competence and work discipline on the performance of civil servants in the District of South Kaliwungu. The population in this research is Civil Servant in Kecamatan Kaliwungu Selatan which amounts to 71 people. In this research using sampling with census technique, because the population is less than 100 people, the sampling technique taken is all members of the population as much as 71 people Civil Service in Kecamatan Kaliwungu Selatan  This data collection through primary data by distributing questionnaires to the object of research and filled Directly by the respondent. As well as secondary data from archives owned by organizations / agencies and literature studies. The analysis method used is data feasibility test, model feasibility test, hypothesis test t-test and multiple linear regression analysis.  otivation has a positive and significant impact on the performance of Civil Servants in Kecamatan Kaliwungu Selatan. Competence has a positive and significant influence on the performance of Civil Servants in Kecamatan Kaliwungu Selatan. Work discipline has a positive and significant influence on the performance of Civil Servants in Kaliwungu Selatan District. Keywords:     work motivation, competence, work discipline and employee performance